Think Globally, Act Locally publishing amidst global summits - Dolly Priatna; Kathryn A. Monk (Universitas Pakuan, 2021)
We are very pleased to present InJAST Volume 2 Number 2 October 2021 at this exciting time for national and global focus on applied environmental studies. This latest edition contains reviews and research articles such as Traditional knowledge of biodiversity in the community surrounding Giam Siak Kecil-Bukit Batu Biosphere Reserve, Riau, Indonesiaâ€ and Overview and evaluation of Indonesia's water resources management policies for food securityâ€. In addition, our guest editorial explores the topic of Government, private, and local communities in ecosystem restoration governance and practicesâ€. This editorial reminds us all that we are now in the first year of the UN Decade on Ecosystem Restoration (2021-2030), which challenges everyone to massively scale up restoration efforts focussed on our degraded ecosystems.